Kebebasan Memperoleh Informasi Dalam Upaya Mewujudkan Transparansi Penyelenggaraan Pemerinthan - Jubaedah, Edah (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2007)
Developed and developing nations around the world yet are recognizing that democracy depends on a free flow of information. International trends toward transparency encourage these nations to provide the legal and regulatory framework, the structures and condition required to guaraantee the right of access to information of their citizens. These nations aware that access to information wheter in the hands of the state of private companies providing public services, help to increase accountability and allow citizens to more fully participate in public life.